Urban geology and environmental problems of Lahore City, Pakistan (Journal of Nepal Geological Society, 2001)
The present study deals with the urban geology and environmental problems of the Lahore City in Pakistan. It is based on a set of the following thematic maps at 1:100, 000 scale: geology, urbanisation, engineering geology, land use, flood hazard, and aquifer drawdown depth. The major hazards of the Lahore metropolitan area are air pollution, water pollution, noise pollution, and deforestation, which are the result of rapid population growth as well as poor planning.The Lahore metropolitan area comprises the Early Pleistocene to Recent silty loess and silty clay deposits of the Ravi River. The foundation conditions of the Lahore metropolitan area are generally good. The city suffers from periodic floods during the monsoon season. The pavement and drains accelerate and increase the surface runoff and the peak flood. Unplanned groundwater development in the metropolis has caused a rapid lowering of the water table. Subsequently, the sand is dewatered and the water table has dropped to 7-13 m.